2021
DOI: 10.1158/1940-6207.capr-20-0262
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Erlotinib Plus Sulindac Dosing Regimens for Intestinal Cancer Prevention in an Apc-Mutant Model of Familial Adenomatous Polyposis (FAP)

Abstract: A clinical trial in patients with familial adenomatous polyposis (FAP) demonstrated that sulindac plus erlotinib (SUL+ERL) had good efficacy in the duodenum and colon, but toxicity issues raised concerns for long-term prevention. We performed a biomarker study in the polyposis in rat colon (Pirc) model, observing phosphorylated Erk inhibition in colon polyps for up to 10 days after discontinuing ERL+SUL administration. In a follow-up study lasting 16 weeks, significant reduction of colon and small intestine (S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…A recent study using a murine model of FAP ( APC -mutation polyposis in rat colon, Pirc) suggested that an optimal low dose strategy (using a human equivalent of erlotinib 125 mg one time per week plus daily sulindac) led to significant tumour inhibition in the colon and small intestine while minimising skin toxicity and gastric ulceration. 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study using a murine model of FAP ( APC -mutation polyposis in rat colon, Pirc) suggested that an optimal low dose strategy (using a human equivalent of erlotinib 125 mg one time per week plus daily sulindac) led to significant tumour inhibition in the colon and small intestine while minimising skin toxicity and gastric ulceration. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Along with the encouraging reductions in duodenal and lower GI polyp burden observed in our study, AEs were frequently A recent study using a murine model of FAP (APC-mutation polyposis in rat colon, Pirc) suggested that an optimal low dose strategy (using a human equivalent of erlotinib 125 mg one time per week plus daily sulindac) led to significant tumour inhibition in the colon and small intestine while minimising skin toxicity and gastric ulceration. 23 To reduce potential bias and interobserver variability, the baseline and 6-month endoscopy were performed by the same endoscopist for all study participants. The endoscopist was not blinded as to whether it was a baseline or endpoint procedure since the placement or existing presence of a tattoo would make it impossible.…”
Section: Gi Cancermentioning
confidence: 99%
“…Future work should seek to corroborate the concentrations of these metabolites in vivo in the context of apoptosis induction in colon tumors after long-term dietary SPI intake, and phenotypic outcomes following treatment of FAP patient organoids. Clinical translation of freeze-dried whole foods, such as SPI, to at-risk patients might provide valuable quality-of-life benefits via inflammasome/immune mechanisms, delaying colectomy and drug intervention [44][45][46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Those with an end ileostomy should have surveillance every 2 years [17]. The role of chemoprevention in management of FAP is actively being studied [18] with promising results for sulindac and erlotinib [19,20,21].…”
Section: Familial Adenomatous Polyposismentioning
confidence: 99%